Reformation - Union - Erweckung: Beispiele aus der Kirchengeschichte Südwestdeutschlands - Benrath, Gustav Adolf (Veröffentlichungen des Instituts für Europäische Geschichte Mainz Abteilung für Abendländische Religionsgeschichte, 2012)
This volume unites contributions by Gustav Adolf Benrath on the history of the church and theology in Southwest Germany. On the occasion of the author´s 80th birthday, the editors have collected 15 of his most important contributions on the history of the Protestant church and theology. The selection process was based on the author´s own research foci, ranging from studies on the influence of the Reformation in Speyer, the Palatinate and Mainz to his work on the Reformed group of Irenics, to the church unions in Mainz, the Palatinate and Baden. There are also contributions on the Basle Mission, the revival movements in Palatine and Baden, on Johann Heinrich Jung-Stilling and Johann Peter Hebel.